2018
DOI: 10.1108/arla-04-2017-0125
|View full text |Cite
|
Sign up to set email alerts
|

Internationalization and performance: the role of depth and breadth

Abstract: Purpose The purpose of this paper is to analyze the relationship between multinationality and firm performance (M-P) in Latin American companies, commonly referred to as multilatinas. The study conceptualizes the depth (intensity) and breadth (geographical scope) of internationalization and examines their effect on financial performance. Although scholars have studied how internationalization in various contexts and industries affects performance, little is known about firms in Latin America. Design/methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 48 publications
1
14
0
2
Order By: Relevance
“…In this regard, depth is measured by financial indicators, including foreign versus total sales, foreign versus total assets, and employees in foreign locations (Abdi & Aulakh, 2018;Brida et al, 2016;Sullivan, 1994). Likewise, breadth refers to the dispersion of offices, branches, and factories located abroad (Velez-Calle et al, 2018). An example of breadth is the number of subsidiaries that a mnc has abroad, the number of employees located in a foreign country, and the number of available rooms abroad (Brida et al, 2016).…”
Section: About Breadth and Depth In Internationalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, depth is measured by financial indicators, including foreign versus total sales, foreign versus total assets, and employees in foreign locations (Abdi & Aulakh, 2018;Brida et al, 2016;Sullivan, 1994). Likewise, breadth refers to the dispersion of offices, branches, and factories located abroad (Velez-Calle et al, 2018). An example of breadth is the number of subsidiaries that a mnc has abroad, the number of employees located in a foreign country, and the number of available rooms abroad (Brida et al, 2016).…”
Section: About Breadth and Depth In Internationalizationmentioning
confidence: 99%
“…One of the first to propose ways to measure doi was Vernon (1971), who proposes a measurement using quantitative indicators. Based on this, the most important measurement currently focuses on quantitative indicators and techniques (Mendoza et al, 2020;Sullivan, 1994;Velez-Calle et al, 2018). Thinking along these lines, the importance of this paper consists in proposing a new way of measuring doi through a qualitative technique of content analysis that will help clarify and deepen the doi topic.…”
Section: Introductionmentioning
confidence: 99%
“…Countries (Cuervo-Cazurra & Dau, 2009). Internationalization and performance: the role of depth and breadth (vélez-Calle et al, 2018).…”
Section: Promarket Reforms and Firm Profitability In Developingmentioning
confidence: 99%
“…Entre el conjunto de las publicaciones bibliográficas abordadas, se destaca una perspectiva orientada a analizar la importancia de la estrategia y la diversificación, en el proceso de internacionalización de empresas latinoamericanas o de países emergentes. Donde factores como la capacidad para profundizar y ampliar el alcance en los mercados internacionales, se convierte en una estrategia que incide en el rendimiento financiero de las empresas latinoamericanas (vélez-Calle et al, 2018); además se plantea a partir de un estudio empírico en compañías multinacionales brasileñas, que el proceso de internacionalización también depende de la capacidad y estrategia de innovación de la empresa (Fleury, Leme & Mendes, 2013); También se aborda la incidencia de los costos de transacción en la estrategia para acceder a mercados exteriores, concluyendo que es más fácil desarrollar mercados regionales que mercados globales dado las restricciones que generan dichos costos de transacción (rugman & verbeke, 2004b).…”
Section: Perspectiva 4: Estrategias Y Competenciaunclassified
“…Previous studies have demonstrated a complex curvilinear relationship between the degree of internationalization (DOI) and performance. The DOI reflects a firm's exports to other countries (Hitt et al 1997;Velez-Calle et al 2018). Many previous studies have investigated the internationalization-performance relationship, with mixed empirical results: positive linear (Delios and Beamish 1999); negative linear (Denis et al 2002;Kim and Mathur 2008); no significant linkage (Majocchi and Zucchella 2003); inverted U-shaped (Elango 2006); U-shaped (Chen and Tan 2012); inverted S-shaped (Cho and Lee 2018); S-shaped (Ruigrok et al 2007); and U-shaped in large firms and W-shaped in small firms (Zhou 2018).…”
Section: The Relationship Between Internationalization Degree and Firmentioning
confidence: 99%